Wavell : The Viceroy's Journal - Edited by Moon, Penderel (Karachi Oxford University Press, 1974)
Lord Wavell's summary dismissal from the post of Viceroy after three and a half years cast a shadow over his achievements and made his efforts appear fumbling and maladroit. This text is intended to correct misconceptions about his tenure and successes as Viceroy, and his personal qualities.
Include Illustrations, Epilogue, Appendices and Index.
It is a biography.
Keywords: Wavell, Archibald Percival Wavell, Earl of, 1883-1950 -- India -- Politics and government